Kontroversi Pemeliharan Jenggot Laki-laki Muslim: Studi Takhrij dan Syarah Hadis - Ferdian Herman; Susanti Vera; Agus Suyadi Raharusun; Husnul Qodim (Gunung Djati Conference Series, 2022)
This study aims to discuss the takhrij and syarah hadith related to the command to lengthen the beard for Muslim men. This study uses a qualitative approach that emphasizes the analysis of literature studies through the takhrij and syarah hadith methods. The results of this study indicate that the quality status of the hadith regarding the command to maintain a beard for Muslim men is of shahi quality because it has met the criteria for the validity of the sanad and the validity of the matan hadith. This hadith is judged to be authentic because all its narrators are at the tsgah level. While the syarah of this hadith shows that the commandment to maintain beards for Muslim men is to distinguish between Muslims and polytheists. From this study it can be concluded that the hadith regarding the command to maintain beards for Muslim men is acceptable so that it can be used as evidence.